The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5935/1415-2762.20140027
|View full text |Cite
|
Sign up to set email alerts
|

Networks to care woven by elderly and her family experiencing situations of chronic illness

Abstract: Redes para o cuidado tecidas por idosa e família que vivenciam situação de adoecimento crônico REME RESUMOO estudo teve por objetivo compreender como se compõem as redes de apoio e sustentação do cuidado tecidas pela família à pessoa idosa que reside sozinha e está em situação crônica de adoecimento. Estudo de caso de abordagem de qualitativa em que foi utilizada a história de vida focal e a entrevista em profundidade como estratégias metodológicas. Para organização e análise dos dados, utilizou-se o desenho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…De acordo com o conceito de unidade de cuidado, a família é definida pelos seus próprios membros. Nesse processo de cuidar, a família se preocupa não somente com o estado de saúde físico do indivíduo doente, mas com seu bem-estar e felicidade (4) . Nesse estudo, considera-se conhecimento como a lembrança de acontecimentos ou fatos transmitidos pelo sistema de educação ao qual o sujeito participa, emitindo conceitos com o entendimento adquirido sobre determinado assunto ou evento (5) .…”
Section: Introductionunclassified
“…De acordo com o conceito de unidade de cuidado, a família é definida pelos seus próprios membros. Nesse processo de cuidar, a família se preocupa não somente com o estado de saúde físico do indivíduo doente, mas com seu bem-estar e felicidade (4) . Nesse estudo, considera-se conhecimento como a lembrança de acontecimentos ou fatos transmitidos pelo sistema de educação ao qual o sujeito participa, emitindo conceitos com o entendimento adquirido sobre determinado assunto ou evento (5) .…”
Section: Introductionunclassified
“…Therefore, as the main care providers, families face demands for care in chronic situations, sometimes by more than one family member. Regarding this experience, some studies (1,(3)(4)(5) have shown the importance of individual provision of care on a continuous basis, whose maintenance requires great effort from families.…”
Section: Formation Of Family Care In Chronic Conditionsmentioning
confidence: 99%
“…Human beings are certainly not, and will never be, completely independent or autonomous, since in certain situations they might need help and support to develop self-care and manage their own lives (1) . If self-care is developed in everyday life and for everyday life, chronic conditions are not separate from it; rather, different levels and duration are increasingly required.…”
Section: Self-care Shaping Family Carementioning
confidence: 99%
See 2 more Smart Citations